KAWASAN DERMAGA WISATA PASAR TERAPUNG MUARA KUIN - Bobby Pistar Sinaga; Rudi Hartono (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2021)
Muara Kuin Floating Market is a place that can boost tourism for science-based markets, which are shrinking and falling. The goal is designed to turn an area that has the value of local culture and the activities of the Banjar tribe so that the jetty area is able to provide a suitable place for tourist destinations where only a few places can exist around the world. The Tourism Area of Muara Kuin Floating Market has a quality as a tourism destination. The Muara Kuin Floating Market Tourism Area is a place where visitors can enjoy tours and visit the Muara Kuin Floating Market which is one of the floating markets praised as the oldest market and is long well-known as the economic center of Banjarmasin City. There is an architectural problem as the floating market jetty area is neglected and disorganized due to the place has been no longer used by the local government. This situation has resulted on ​​the area of ​​Muara Kuin to be less known to many people. To achieve the goal as the Muara Kuin Floating Market Tourism Area, a "Conceptual" concept is applied and "Programming" design method is aimed at reviving the Floating Market Area and to accommodate the related activities in order to restore the characteristics determining the area and to support the area development. The goal is achieved by making the area which has local cultural elements and Banjar tribal activities so that it is able to provide a suitable tourism place which is only a few found in the world. By applying the concepts and design methods in order to be able to provide an attraction to the area and is expected to be able to overcome problems and achieve the objectives of the design of the Muara Kuin Floating Tourism.